Molecular and morphological confirmation of Profilicollis altmani as the cause of acanthocephalan peritonitis in California sea otters (Enhydra lutris nereis) - Richard E. Grewelle; Katherine Greenwald; Colleen Young; Melissa Miller (International Journal for Parasitology: Parasites and Wildlife, 2023)
Acanthocephalan peritonitis (AP; trans-intestinal migration of acanthocephalan parasites into the peritoneal cavity resulting in severe peritonitis), is a common cause of mortality in southern sea otters (Enhydra lutris nereis). Although Profilicollis spp. acanthocephalans have been implicated in these infections, the species causing AP has been an important unresolved question for decades. We used morphological and molecular techniques to characterize acanthocephalans from the gastrointestinal (GI) tract and peritoneal omentum of eighty necropsied southern sea otters. Only P. altmani was found to have perforated through the intestinal wall and migrated into the peritoneal cavity of examined sea otters, resulting in AP. Morphological and molecular criteria confirmed that Profilicollis kenti was synonymous with P. altmani. A second Profilicollis sp., likely P. botulus, was present only in the intestinal lumen, did not penetrate through the intestinal wall, and was not associated with AP.